Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.